Single nucleotide polymorphisms in the D-loop region of mitochondrial DNA is associated with colorectal cancer outcome. (1st November 2016) - Wang, Cuiju; Zhao, Shengnan; Du, Yanming; Guo, Zhanjun
Abstract: Single nucleotide polymorphisms (SNPs) in the displacement loop (D-Loop) of mitochondrial DNA (mtDNA) has been identified for their association with the risk and outcome in many cancers. We have identified risk associated D-loop SNPs for colorectal cancer previously, in the present study, we evaluate their prognostic value for postoperative survival of colorectal cancer (CRC). The minor haplotype of nucleotides 16290T and frequent haplotype of nucleotide 16298T in the hypervariable segment 1 (HV1) region of the D-loop were identified for their association with high survival rate of CRC. After adjusted with COX proportional hazard model, the nucleotide site of 16290 was identified as independent predictor for CRC (RR, 0.379; 95% CI, 0.171–0.839; p = 0.017). In conclusion, SNPs in the mtDNA D-Loop were found to be valuable markers for colorectal cancer outcome evaluation.